Tren Kejadian Dengue (Incidence Rate) dan Kematian Akibat Dengue (Case Fatality Rate) di Indonesia - Meyrita, Meyrita; Suwarno, Suwarno; Saidi, Nurdin; Razi, Nanda Muhammad (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Dengue Hemorrhagic Fever (DHF) is a disease that currently has significant morbidity and mortality rates. In Indonesia, the trend of DHF cases has increased and decreased every year. This study aims to analyze the development of dengue cases by considering two indicators, namely dengue incidence rate and dengue case fatality rate (CFR) during the period 2012-2022, to know the pattern of dengue disease in Indonesia, and evaluate the government's target in handling dengue cases based on IR and CFR rates. The data used is secondary data obtained from the 2021 Indonesian Health Profile and the 2022 Dengue Fever Annual Report. IR and CFR data were analyzed using Microsoft Excel which will be interpreted in the form of graphs to illustrate the trends and patterns of DHF cases in Indonesia, IR maps in 2021 and 2022 were analyzed using ArcGIS software. Based on the results of the analysis, the development of dengue cases during the period 2012-2022 experienced a misalignment between the increasing trend of IR and CFR. The IR value experienced significant fluctuations from 37.3 per 100,000 population in 2012 to 52.07 per 100,000 population in 2022, while the CFR value during the period 2012-2022 tended to decrease from 0.90% (2012) to 0.86% (2022). This pattern reflects the complex dynamics of DHF epidemiology, where an increase in cases is not always followed by an increase in fatalities. The IR and CFR achievements for 2022 have not met the government's expectations, with only 16% of districts/cities having IR values â‰¤ 10/100,000, while the CFR value reached 0.86%, slightly above the set target of 0.7%.